Infant and young child feeding practices among mothers in Hyderabad, Telangana - Mane, Sudhir Shankar; Chundi, Pranitha Reddy (International Journal Of Community Medicine And Public Health, 2017)
Background: The objective of the study was to assess Infant and Young Child Feeding (IYCF) practices using World Health Organization indicators in infants and young children attending immunization clinics. Methods: A hospital based cross-sectional study was designed in a tertiary care hospital in an urban setup. Infant and young children from birth to 24 months attending immunization clinics were included. Main outcome measures were to assess IYCF Practices (8 Core and 7 Optional Indicators) and possible reasons for not practicing the same. Results: A total of 520 mothers attending immunization clinics were interviewed from June to July 2014. Mean age of the children was 32.5 weeks. 50.1% and 47.6% belonged to Hindu and Muslim religion respectively. Only 33.78% children were breastfed within one hour of birth. Among those who had not initiated breastfeeding within one hour of birth, 60.6% were not aware and the most common reason was caesarean section. In children older than 6 months, only 80% of children were exclusively breast fed for six months and the most common reason was insufficient breast milk. Only 72.5% of mothers introduced complementary foods from 6 to 9 months. Conclusions: The study shows poor IYCF practices in children attending immunization clinic at an urban tertiary care hospital. There is a clear knowledge gap among mothers. These faulty practices need to be addressed to improve feeding practices so as to maximize their benefits to the child. The study did not assess nutritional status of children. This would have been useful to see how inadequate IYCF practices were associated with nutritional status of the children.